The Effect of Earning Management and Good Corporate on Tax Avoidance on Retails and Investment Companies on Indonesia Stock Exchange (BEI) in 2018 - Khairul Arief Rachman; Ati Sumiati; Achmad Fauzi (LPPM Universitas Negeri Jakarta, 2020)
This research intends to know an affection between earning management, good corporate governance, on tax avoidance in retails and investment sector companies that have been listed on the Indonesia Stock Exchange in 2018 and focused on tax avoidance as one of the strategies for tax management. The research method used is the quantitative method. The type of data research is secondary data obtained using documentation techniques through the company’s financial statements with 85 samples. The data analysis technique using the requirements analysis test, classic assumption test, multiple regression test, and hypothesis test. The partial hypothesis test results show that capital intensity has a positive and significant effect on tax management; profitability, firm size, and leverage has no significant effect on tax management. Based on the analysis that has been done gives the result that Earning Management and Good Corporate Governance have a negative simultaneous effect on Tax Avoidance. As for testing the partial hypothesis, both good corporate governance and earning management have a negative effect but good corporate governance has a significant effect on tax avoidance while earning management is not.